Pimelodus maculatus e P. platicirris (Siluriformes: pimelodidae) no alto rio Paraná: caracterização morfológica, dieta e reprodução - Silva, Thiago Teixeira [UNESP] (2015)
Pimelodus maculatus e P. platicirris are sympatric species and the first the most abundant specie of the genus in the upper Paraná river. They have similar morphological patterns and P. platicirris has been wrongly identified as P. maculatus. In this study we compared them morphologically and describe their differences. Pimelodus platicirris lacks basic information about their biology. Therefore, we describe the diet and reproduction of both species and compared them. They differ by color patterns and some morphological features as the height of adipose fin, height and length of the head and body height. Their diets were composed basically of the same food items, but differed in frequency of items consumed. Both are omnivorous with high plasticity of feeding habitats. The absence of gonads in advanced maturation stage did not allow us to determine the reproduction period, nor to affirm if the sampled stretch is used as a site of reproduction